Application of Politeness Theory in Digital Communication: Impacts and Implications for Online Interactions - Suerni, Suerni (PT Inovasi Pratama Internasional, 2024)
The objective of this research is to gather data pertaining to the significance of polite language usage on social media platforms and the influence of impolite language on social media interactions. This research, which focuses on language politeness in social media, employs a qualitative research method that collects data and then analyzes it in a way that produces a complete written work. The source data for this research are obtained from a variety of websites offering related information and a number of published works addressing the same background. The analysis of these diverse sources is an essential component of the research process. The findings presented here are limited to an investigation of social media, polite language, and the potential implications of applying politeness theory in everyday life. The data collected for this study was analyzed and sorted into categories that can be used as material for this research project's writing. From these analyses, it can be concluded that there is a notable influence of polite language in the digital media world and its impact on everyday life. The implementation of politeness in digital language has a positive influence in real life, as observed in this study.